Ore deposits : origin, exploration, and exploitation - Decrée, Sophie; Robb, Laurence (Geophysical monograph, 2019)
The latest knowledge on mineral ore genesis and the exploration of ore deposits Global demand for metals has risen considerably over the past decade. Geologists are developing new approaches for studying ore deposits and discovering new sources. Ore Deposits: Origin, Exploration, and Exploitation is a compilation of diverse case studies on new prospects in ore deposit geology including atypical examples of mineral deposits and new methods for ore exploration. Volume highlights include: -Presentation of the latest research on a range of ore deposit types -Application of ore deposits to multiple areas of geology and geophysical exploration -Emphasis on diverse methods and tools for the study of ore deposits -Useful case studies for geologists in both academia and industry Ore Deposits: Origin, Exploration, and Exploitation is a valuable resource for economic geologists, mineralogists, petrologists, geochemists, mining engineers, research professionals, and advanced students in relevant areas of academic study.